From Geotechnical Data to GeoBIM Models: Testing Strategies for an Ex-Industrial Site in Turin - Arianna Fonsati; Renato Maria Cosentini; Chiara Tundo; Anna Osello (Buildings, 2023)
Over the years, the use of Building Information Modelling (BIM) methods has changed the workflows of various actors, providing better integration across different domains and allowing for new ways of working. This paper outlines the interest towards the integration of BIM with geotechnical/geological modelling (GeoBIM), which still represents a major challenge in several respects. The present study aims to provide a flexible method for assessing various integration strategies and to establish a preferred workflow based on the selected requirements and preference parameters. This integration is designed to provide a final federated model that can also be archived in the as-built documentation. Four alternative processes were selected to analyse the specific types of data and transformations required in the process. Each process was applied on a real case study in order to test the developed assessment framework using the Analytical Hierarchy Process (AHP). Due to technological advances, modelling and integration workflows change rapidly; however, our results show that the proposed evaluation framework is universal and adaptable to any new integration approach. Further research efforts must be undertaken to reduce attribute data losses and enhance the interoperability between systems and professionals.